A fully integrated approach to blended language learning - Vičič, Polona (ELOPE (Ljubljana), 2020)
In the face of increasing demand for greater continuity and flexibility in language learning, online learning has gradually established itself as an important complement to face-to-face (F2F) language instruction. Typically, the resulting blend focuses on the two central learning modes, i.e., F2F and online; however, it leaves out the self-study component based on sources that do not form an integral part of the online component. Recognising the importance of the latter, Whittaker (2014) defines blended language learning as a blend of F2F, online, and self-study components. Drawing on this three-modal approach, the present paper first outlines two language courses designed and delivered by the author of the paper. Next, it analyses students' feedback on their experience with blended learning collected via an end-of-course questionnaire including multiple-choice statements, five-point Likert scale statements, and open-ended questions. The sample included fifty-two students, most of whom reported a positive experience, especially with the F2F component.
Keywords: blended language learning; celostni pristop; continuity; fully integrated approach; kombinirano jezikovno učenje; kontinuiteta; three-modal approach; trimodalni pristop